A study comparing positive benefits for parents, and their children, of children attending the UK’s holiday activities and food program to parents of non-attendees - Defeyter, Margaret Anne; Stretesky, Paul B.; Pepper, Gillian V. (Frontiers in Public Health, 2025)
The Holiday Activities and Food (HAF) is a UK Department for Education (DfE) funded program that provides free food and activities for 5–16-year-olds in receipt of means-tested free school meals. This evaluation focuses on parent/caregiver perceptions of HAF benefits during the 2021 and 2022 school holidays for a sample of parents/caregivers whose children attended HAF (n = 736) and a sample who did not attend HAF (n = 885). The results show that parents of children who attend HAF for 4 weeks (i.e., the ‘4-Week’ HAF treatment group) report that their children engage in more weeks of physical activity compared to children in the Non-Attendee group (b = 0.59, 95% CI [0.25, 0.94]). Parents/caregivers of children who attended HAF for 6 weeks or more report no significant difference in household food insecurity compared to parents/caregivers in the Non-Attendee group (b = −0.27, 95% CI [−0.70, 0.16]). The results also show that parents/caregivers are more concerned about affordable childcare if their children attend 6 weeks or more of HAF (b = −1.33, 95% CI [−2.07, −0.59]). For parents and caregivers of children who attend HAF for 1 to 5 weeks there is no difference in self-reported Parental Wellbeing compared to parents/caregivers of non-attending children (b = 0.57, 95% CI [−0.09, 1.23]), but parents/caregivers whose children attend 6 weeks or more of HAF report significantly better wellbeing than parents in the control group (b = 1.12, 95% CI [0.56, 1.69]). Parents and caregivers of attendees in the HAF treatment groups are no more or less likely to believe that children are safe in their neighborhood than in the Non- Attendee group (b = 0.12, 95% CI [−0.11, 0.34] for 6 or more weeks of attendance vs. non-attendees). These findings are discussed in relation to prior research, and we make several HAF policy recommendations.